The Normative Structure of the State of Epidemic under Polish Law - Bosek, Leszek (Medicine, Law & Society, 2021)
This article analyses normative structure of a key anti-epidemic emergency measure under Polish law – a State of Epidemic. It is defined as a legal situation introduced in a given area in connection with an epidemic in order to undertake anti-epidemic and preventive measures specified in the Act of 5 December 2008 on preventing and combating infections and infectious diseases to minimize the effects of the epidemic. The Act and this complex measure is authorised by Article 68(4) of the Constitution of the Republic of Poland of 2 April 1997. It requires public authorities to “combat epidemic illnesses and prevents the negative health consequences of degradation of the environment“. The purpose of this article is also to explain why Poland reacted to the SARS-CoV-2 crisis declaring the nationwide State of Epidemic on 20 March 2020 and not by other extraordinary measures.